KEAKURATAN MODEL ARUS KAS METODE LANGSUNG DALAM MEMPREDIKSI ARUS KAS DAN DIVIDEN MASA DEPAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2009-2012) - Efris Saputri, Eka Julianti; Afiani, Desi; Bawamenewi, Faaduhu (JURNAL RISET AKUNTANSI JAMBI, 2020)
The research was perfomed to determine the accuracy of the direct method cash flow models in predicting future cash flow and dividend. This study aims to test the accuracy of the models direct cash flow method in predicting future cash flow and dividend. The study evaluated cash flow and dividend prediction models, that employed cash inflows from operating activities and cash outflows for operating activities. Populations in the study are all of manufacturing firmsthat listen on Indonesian Stock Exchange in the period of 2009-2021. In this study, samples taken by purposive sampling metod on certain criteria. the research gets 15firms from 131 firms which mathc with criteria. Establishment of Prediction Model using Ordinary Least Squares regression analysis, and hypothesis testing done with test Paired Samples T-Test. The results of this study showed that the models of the direct method cash flow accurately in predicting future cash flow and dividend.